6th International Symposium on Tonal Aspects of Languages (TAL 2018) 2018
DOI: 10.21437/tal.2018-23
|View full text |Cite
|
Sign up to set email alerts
|

Production and Perception of Rising Tone Sandhi in Mizo

Abstract: Mizo, a Tibeto-Burman language of the Kuki-Chin group is primarily spoken in the northeast Indian state of Mizoram in Northeast India. Mizo has four lexical tones, namely, high (H), rising (R) , falling (F) and low (L). Mizo tones are mostly dynamic, except the H tone which is a static tone. Previous researches have reported that the rising tone in Mizo changes into low tone when it is followed by either high tone or falling tone which is regarded as rising tone sandhi. The present study analyzes the productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The salient characteristics of Mizo tones also aid automatic speech recognition in noisy conditions [20]. Apart from the four phonological tones, in a previous study, evidence of another salient Mizo tone resulting from tone sandhi is also mentioned [21].…”
Section: Introductionmentioning
confidence: 85%
“…The salient characteristics of Mizo tones also aid automatic speech recognition in noisy conditions [20]. Apart from the four phonological tones, in a previous study, evidence of another salient Mizo tone resulting from tone sandhi is also mentioned [21].…”
Section: Introductionmentioning
confidence: 85%
“…In case of noisy speech conditions, the vocal tract information gets severely affected, yet the fundamental frequency (F0) information is largely retained. Drugman et al [8] reported that The data involved in this tonal analysis is described in [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a method for automatic detection of tones was proposed, resulting in about 70% accuracy incorrect classification of the four tones in Mizo [17]. Apart from the four canonical tones, there is tone- sandhi in Mizo where the presence of high and falling tone after a rising tone lowers the F0 of the rising tone [11,12,15,18]. The remainder of the paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%